The image of the hero in the novel (Strand of Days by the writer "Zakaria Ishriqi" - رشواني, بدر; فاخرصالح ميَّا (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
TheArabic novel occupied a prominent position globally and was able to establish a set of artistic characteristics, which made it distinguished from other arts, and this is for its artistic construction of place, time, conflict and characters, the latter which is among the important structures, and this is because of the presence of the heroine character that moves the conflict, so no novel is devoid of the presence of a hero who is the basic building block and the main axis in any literary work. This study comes with the aim of providing a sufficient perception of the term hero and heroism, and its most important components in the Arabic novel in the novel (Pomegranate Flower) by the writer "Zakaria Shriqi", and this term formed a turning point in the writings of researchers, and their cause as a highlight of the stage of peace or wading into the midst of a psychological situation experienced by the hero, and the extent of the hero's response to the variables of the reality he lives.